Catalytic Activity, Stability, Unfolding, and Degradation Pathways of Engineered and Reconstituted Myoglobins - RONCONE, RAFFAELLA; MONZANI, ENRICO; Labò S.; Sanangelantoni A. M.; CASELLA, LUIGI (JBIC Journal of Biological Inorganic Chemistry, 2005)
The structural and functional consequences of engineering a positively charged Lys residue and replacing the natural heme with a heme-L-His derivative in the active site of sperm whale myoglobin (Mb) have been investigated. The main structural change caused by the distal T67K mutation appears to be mobilization of the propionate-7 group. Reconstitution of wild-type and T67K Mb with heme-L-His relaxes the protein fragment around the heme because it involves the loss of the interaction of one of the propionate groups which stabilize heme binding to the protein. This modification increases the accessibility of exogenous ligands or substrates to the active site. The catalytic activity of the reconstituted proteins in peroxidase-type reactions is thus significantly increased, particularly with T67K Mb. The T67K mutation slightly reduces the thermodynamic stability and the chemical stability of Mb during catalysis, but somewhat more marked effects are observed by cofactor reconstitution. Hydrogen peroxide, in fact, induces pseudo-peroxidase activity but also promotes oxidative damage of the protein. The mechanism of protein degradation involves two pathways, which depend on the evolution of radical species generated on protein residues by the Mb active species and on the reactivity of phenoxy radicals produced during turnover. Both protein oligomers and heme-protein cross-links have been detected upon inactivation.